Effectiveness of Microfinance Banks in Alleviating Poverty in Kwara State Nigeria (Global Journal of Management and Business Research, 2011)
Abstracts -Microfinance banks supply loans, savings and other financial services to the poor and low income population on a sustainable basis and help in the alleviation of poverty. This article therefore examines the effectiveness of microfinance banks in alleviation of poverty in Kwara state Nigeria. The data collected were analyzed through the use of t-test and Analysis of Variance (ANOVA). From the research findings, results revealed that microfinance has significant role to play in the economy, as it helps reduce poverty by providing financial services to the active poor, help in generating employment and also provide small loans to grow small businesses. It is therefore recommended that regulatory and other statutory bodies should monitor the interest rate on loans and advances to make it accessible to micro-clients that is the economically active poor. Government should make available necessary infrastructural facilities that will help increase the output of micro entrepreneurs. Also, Microfinance policy should further be publicized so that members of low income groups will be aware of what microfinance institutions have to offer them and how they can obtain financial services to grow their small businesses.
Keywords: Microfinance banks; Alleviating; Poverty; Active poor; Nigeria